Monastic Musical Fragments from Iceland - Attinger, Gisela (Religions, 2021)
Little has survived from medieval liturgical books in the Nordic countries other than fragments. It is often difficult, if not impossible, to state their exact provenance, but the contents sometimes indicate that they once belonged to a monastic institution. The article presents some of these sources, focusing on two fragments with music for the celebration of St Olav from Iceland and Sweden which show how an already established sequence of songs was adapted to fit the liturgical needs of a monastic community. In addition, it briefly presents two other Icelandic sources that follow monastic use and can shed more light on musical traditions in the Icelandic monasteries in the Middle Ages.